WiMAX - Rao, G. S. V.; Radhamani, G. (Auerbach Publications, 2007)
The demand for broadband connectivity is growing rapidly, but cannot be met effectively by existing wireline technology. WiMAX has the potential to provide widespread Internet access that can usher in economic growth, better education and healthcare, and improved entertainment services. Examining the technology's global development and deployment a.